The political economy of classical Athens : a naval perspective - O'Halloran, Barry, (Mnemosyne, Supplements, 2019)
Recently there has been a welcome revival of scholarly interest in the economy of classical Greece. In the face of increasingly compelling arguments for the existence of a market economy in classical Athens, the Finleyan orthodoxy is finally relinquishing its long dominion. In this book, Barry O'Halloran seeks to contribute to this renewed debate by re-interrogating the ancient evidence using more recent economic interpretative frameworks. The aim is to re-evaluate accepted orthodoxies and present the economic history of this emblematic city-state in a new light. More specifically, it analyses the economic foundations of Athens through the prism of its navy. Its macroeconomic approach utilises an employment-demand model through which enormous naval defence expenditures created an exceptional period of demand-led economic growth.